Margaret Olley : far from a still life - Stewart, Meg, 1948- (North Sydney, NSW : Random House Australia Pty Ltd, 2012)
With new chapters taking in the last few years of Margaret Olley's life, her state funeral and the enormous legacy she has left behind. 'A great painter, a great woman, a great story' Barry Humphries Margaret Olley is arguably Australia's most loved artist. She was also one of the country's most generous benefactors to public art galleries. This intimate biography begins in the 1920s in the green, tropical wet of Tully, North Queensland, where Margaret's early childhood was spent on a cane farm and dairy. The story unfolds to tell of her life-long love affair with painting. At boarding school at Somerville House, Brisbane, Margaret found a mentor in art teacher Caroline Barker, and she went on to blossom as an art student at East Sydney Technical College. The book includes intriguing revelations about her friendships with well-known figures such as Donald Friend, William Dobel and Russell Drysdale, and the success of her first one-person show in Sydney at the age of twenty-five. Bohemian adventures in Europe with fellow Australian artists, including David Strachan, were to follow. She travelled - sketchbook in hand - around England, France, Italy and Spain; met Alice B. Toklas in Paris; and lived on a vineyard at Cassis in the South of France. Her story continued back in Australia where in the late 1950s in Brisbane Margaret struggled with alcoholism and was eventually forced to face up to drying out or drying up creatively. Once she'd given up her comforting nips, her return to life and painting was joyous. This is a rich and comprehensive look at eighty-odd years of Margaret Olley, her lovers and friends, and, of course, her painting.
First published by Random House Australia in 2005.
Imprint: RHA eBooks Adult.
Includes bibliographical references and index.
Audience: General.
Keywords: Olley, Margaret, -- 1923-2011.; Painting, Modern -- 20th century; Women painters -- Australia -- Biography; Biography & Autobiography - Entertainment & Performing Arts; Biography: arts & entertainment; Australian; Biographies